Application of structural equation model in explaining the role of cognitive flexibility, emotional self-regulation and actively open-minded thinking on changing people\'s attitudes - ebrahim Chellemal Dezfooli Nejad; farzan momeni; mir mohsen pedram; alireza moradi (مجله علوم روانشناختی, 2021)
Background: Due to the growing trend of social networks and the expansion of their impact, studies have been conducted on the impact of these networks on attitudes, behaviors and lifestyles, etc. However, no study has been done on the effect of cognitive indicators on attitude change in social networks. Aims: The purpose of this study is to present a conceptual model to examine the effect of three factors: (1) cognitive flexibility, (2) emotional self-regulation, and (3) actively open-minded thinking on changing people's attitudes in social networks. Methods: The method of the present study is descriptive.Data collection was done via survey method. The statistical population includes all users of social networks. The statistical sample included 384 men and women who were selected by convenience sampling. To examine the effect of cognitive flexibility, emotional self-regulation, and actively open minded thinking on attitude change, following three scales were used respectively, Martin and Rubin Cognitive Flexibility Scale (Martin and Rubin, 1995), Emotional Self-Regulation Questionnaire (Hoffman, & Kashdan, 2010), Actively Open-Minded Thinking Questionnaire (Stanovich &West 2007). The attitudes of individuals was examined by researcher-made questionnaires whose content validity was confirmed by experts and their reliability was confirmed by statistical methods. After confirming the normality of the data, structural equation modeling with lisrel software was used. Results: Testing the hypotheses performed by structural equations showed that mentioned indicators have an acceptable t value at a significant level (p <0.05). Therefore, they are effective in changing people's attitudes. Emotional self-regulation was also shown to have the greatest effect (0.9) on changing attitudes toward domestic violence. Conclusion: This means that the cognitive abilities of social network users have a direct impact on changing their attitudes.